O uso de aplicativo Web como facilitador da aprendizagem para o ensino de Termometria e Energia Térmica - Torres, Luís Otávio Ramos (2017)
This work aims to create a Web Application, described in the Java programming language, which aims to give greater objectivity to the teaching of Thermology for high school students, inserting them in this science in a more practical and objective way, seeking, through Research on topics of interest, create a simpler view about physics and then awaken a willingness in high school students to learn and better understand the subjects addressed by them in their academic trajectory. For this, we used the teaching-learning methods: just in time Teaching Instruction and peer Instruction. We applied our product in three high school classes of a private school in Cuiabá-MT. The material developed and the choice of teaching methods were subsidized by the Significant Learning Theory of Ausubel. We used the following dynamics in our work: the students read a supporting text, which we elaborated, on the subject we were working on. We suggested to a Portuguese teacher that she used a class of her to interpret, with the students, the text that we elaborated. After the interpretation class, we applied the pre-test. Based on the result of this pre-test, we prepared and taught the actual physics class, emphasizing the points that the students had the greatest difficulty. After that, we did the class where we used our product that configured the post-test. Finally, we applied to the students a questionnaire evaluating the methodology that we used in our work. After analyzing the collected data, we can say that there was evidence of significant learning of the concepts addressed.